2004
DOI: 10.1111/j.1048-891x.2004.14517.x
|View full text |Cite
|
Sign up to set email alerts
|

Do the pelvic lymph nodes predict the parametrial status in cervical cancer stages IB-IIA?

Abstract: The aim of this study was to determine whether the pelvic lymph nodes would predict the parametrial status in patients with cervical cancer stages IB1-IIA submitted to radical surgery and pelvic lymphadenectomy. To this end, we evaluated the relationship between positive and negative pelvic lymph nodes and their parametria. Our final purpose was to use this information to recommend the tailoring of the parametrial resection according to the status of pelvic lymph nodes to decrease the morbidity related with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
(86 reference statements)
0
11
0
4
Order By: Relevance
“…Kodama et al, reported that pelvic lymph node status is the strongest independent predictor of parametrial involvement [14]. Similarly, Puente et al, suggested that pelvic lymph node status is a good predictor of parametrial involvement in node-negative patients in whom less radical surgery could be used [15]. In our study, we found that LVSI, deep cervical stromal invasion, lymph node metastasis, and tumor size are significant risk factors for parametrial involvement in patients with clinical early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Kodama et al, reported that pelvic lymph node status is the strongest independent predictor of parametrial involvement [14]. Similarly, Puente et al, suggested that pelvic lymph node status is a good predictor of parametrial involvement in node-negative patients in whom less radical surgery could be used [15]. In our study, we found that LVSI, deep cervical stromal invasion, lymph node metastasis, and tumor size are significant risk factors for parametrial involvement in patients with clinical early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Out of the 62 patients who were operated, 28 patients received adjuvant RT, 23 for lymph nodal metastasis (LNM) [out of which 9 also had occult parametrial metastasis (OPM)] and 5 patients for presence of two or more intermediate risk factors (LVSI, PTD>2cm, DSI). 5,7,8 However, Benedetti-Panici et al in their study of patterns of parametrial involvement and LN metastasis found that lateral parametrium was the most common site of PM and that too by tumor embolization and hence OPM could occur independently and unpredictably in both lateral and medial parametrium. This led sceptics to believe that entire parametrium needs to be routinely removed irrespective of other factors though Puente et al has contradicted this finding in their study.…”
Section: Resultsmentioning
confidence: 99%
“…This led sceptics to believe that entire parametrium needs to be routinely removed irrespective of other factors though Puente et al has contradicted this finding in their study. 2,7 It has also been debated whether taking a chance with oncological safety is going to benefit the patient significantly? The entire purpose of limiting the radicality of parametrial resection is to avoid possible long-term complications (Fistulae, bladder dysfunction, anal dysfunction and sexual dysfunction) that occur due to visceral damage and injuries to autonomic nerves and the complications of fibrosis and endarteritis especially after adjuvant RT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se encontró que el estado ganglionar linfático pélvico es el predictor independiente más fuerte para presentar CP, conjuntamente con la profundidad de infiltración. Este factor ha sido previamente reportado como un predictor sólido de propagación parametrial (7,18,(21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Discussionunclassified